2013
DOI: 10.1007/s00401-013-1218-2
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative multidimensional molecular analyses of pediatric diffuse intrinsic pontine glioma reveals distinct molecular subtypes

Abstract: Diffuse Intrinsic Pontine Glioma (DIPG) is a highly morbid form of pediatric brainstem glioma. Here, we present the first comprehensive protein, mRNA, and methylation profiles of fresh frozen DIPG specimens (n=14), normal brain tissue (n=10), and other pediatric brain tumors (n=17). Protein profiling identified 2,305 unique proteins indicating distinct DIPG protein expression patterns compared to other pediatric brain tumors. Western blot and immunohistochemistry validated upregulation of Clusterin (CLU), Elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 54 publications
4
108
0
2
Order By: Relevance
“…4). For example, a set of three complement related genes -complement C3, α-2 macroglobulin (A2M) and the complement lysis inhibitor SP-40/clusterin (CLU) -that have been implicated in various cancers including gliomas (Reis et al 2018;Saratsis et al 2014;Shinoura et al 1994;Suman et al 2016) were present in this group, and interestingly, these three proteins have been recently shown to form a network of related biomarkers in B-ALL (Cavalcante Mde et al 2016). One tumor contained a cluster of highly .…”
Section: Genes Showing Somatic Mutations In Multiple Tcga Samples Onlmentioning
confidence: 99%
“…4). For example, a set of three complement related genes -complement C3, α-2 macroglobulin (A2M) and the complement lysis inhibitor SP-40/clusterin (CLU) -that have been implicated in various cancers including gliomas (Reis et al 2018;Saratsis et al 2014;Shinoura et al 1994;Suman et al 2016) were present in this group, and interestingly, these three proteins have been recently shown to form a network of related biomarkers in B-ALL (Cavalcante Mde et al 2016). One tumor contained a cluster of highly .…”
Section: Genes Showing Somatic Mutations In Multiple Tcga Samples Onlmentioning
confidence: 99%
“…Although DIPG shares recurrent aberrations in histone 3 genes with supratentorial pediatric gliomas, they are molecularly distinct tumors [42,43,49]. DIPG is characterized by unique hallmarks including a remarkable spatiotemporal specificity (occurring in the ventral pons during mid-childhood) and a diffuse growth pattern.…”
Section: Introductionmentioning
confidence: 99%
“…5 Moreover, genomic analyses have shown that even within a single demographic group or histological entity, multiple molecular subtypes of disease exist. 6,7 Our increased understanding of the molecular characteristics underpinning glioma pathogenesis and increased precision in defining disease subsets will hopefully lead to the development of treatments that target the molecular aberrations driving their genesis. However, to fully achieve the promise of precision medicine, it will be necessary to use preclinical models that match specific disease subsets not only in terms of pathology and demographics, but on genetic mechanisms as well.…”
Section: Human Gliomas Are Genomically Heterogeneousmentioning
confidence: 99%